Acantholimon akaydinii (Plumbaginaceae), a new species of A. section Staticopsis from Eastern Anatolia - Özüdoğru, Bariş; Özgi̇şi̇, Kurtuluş (Phytotaxa, 2022)
Acantholimon akaydinii, from Darende district of Malatya Province in eastern Anatolia (Turkey) is described as a new species based on morphological evidence. It resembles the recently described A. ibrahimii but can be readily distinguished by several morphological characters including longer, much-branched scapes and paniculate inflorescence, shorter scales, shorter spikelets, shorter calyx, and pink petals, among others. Diagnostic morphological characters, a full description, a revised key to the Turkish Acantholimon species of A. sect. Staticopsis with laxly distichous spikes, and scape much longer than leaves, as well as  detailed illustrations are provided. Furthermore, the IUCN Red List category of the new species is assessed as Critically Endangered (CR) due to its limited distribution and true agricultural pressure.